Optimizing the Role of Community Guidance Officers as the Vanguard of the Juvenile Justice System - Ria Anggraeni Utami; Randy Pradityo; Helda Rahmasari; Riska Karinda (Unnes Law Journal, 2024)
One provision in the juvenile justice system is that juvenile justice proceedings must involve Community Guidance Officers from correctional institutions (BAPAS) who conduct social investigations on the child, which serve as considerations in the juvenile justice process. However, the presence of Community Guidance Officers has received inadequate attention so far, as if the main actors in handling troubled children are only the Police, Prosecutors, Judges, and LPKA officers. The research method used is empirical juridical research, conducted through field research and literature review. The role of Community Guidance Officers in the Legal Jurisdiction of Bengkulu Province as the Vanguard of the Juvenile Justice System is to provide assistance and recommendations for handling children by conducting social investigations from pre-adjudication, adjudication, to post-adjudication. The obstacles faced by Community Guidance Officers in Bengkulu Province include lack of competence and uniformity in law enforcement officials' perception regarding the best interests of the child, incomplete implementation of recommendations due to lack of facilities for child placement, and societal stigma against the child. Additionally, there are technical obstacles such as distance between BAPAS Bengkulu and the child's residence area. Efforts to optimize the role of Community Guidance Officers in Bengkulu Province involve aligning law enforcement officials' perception regarding the best interests of the child, raising awareness among communities and relevant institutions to accept these children, establishing BAPAS posts, and optimizing the role of local governments to synergize government programs in combating juvenile crime.